Kunstlijn 1993 : Zomermanifestatie. (Dalfsen : Stichting Beeldenroute Overijssel, 1993)
van Munster, Jan ; Heemskerk, Cees ; Kessler, David ; Bloom, Barbara ; Merz, Gerhard ; Appel, Karel ; Müller, Pjotr ; Kosuth, Joseph ; etc.
Zomermanifestatie Kunstlijn 1993, Zwolle - Dalfsen - Ommen - Gramsbergen, 1993
Nederlands
kunstcatalogus